The impact of innovation and information technology on greenhouse gas emissions: A case of the Visegrád countries - Radosław Miśkiewicz (Journal of Risk and Financial Management, 2021)
The rapid growth of negative consequences from climate changes provokes divergent effects in all economic sectors. The experts proved that a core catalyst which bootstrapped the climate changes was greenhouse gas emission. This has led to a range of social, economic, and ecological issues. Such issues could be solved by extending innovation and information technology. This paper aimed to check the hypothesis that innovation and information technology allowed for a reduction of greenhouse gas emissions. The author used such methodology as OLS, fully modified OLS (FMOLS), dynamic OLS (DMOLS), Dicky-Fuller and Phillips-Perron tests. The research is informed by the report of the World Economic Forum, World Data Bank, Eurostat for the Visegrád countries (Hungary, Poland, Check Republic, Slovakia) for the period of 2000-2019. The findings were confirmed in models without control variables, and an increase of 1% of patents led to reducing greenhouse gas (GHG) emissions by 0.28% for Poland, 0.28% for Hungary, 0.38% for the Slovak Republic and 0.46% for the Czech Republic. At the same time, for the models with control variables, only Hungary experienced a statistically significant impact. There, an increase of patents by 1% led to reduction of GHG emissions by 0.22%. The variable R&D expenditure was statistically significant for all countries and all types of models (with and without control variables). The increase of R&D expenditure provoked a decline of GHG emissions by 0.29% (without control variables) and 0.11% (with control variables) for Poland, by 0.26% (without control variables) and 0.41% (with control variables) for Hungary, by 0.3% (without control variables) and 0.23% (with control variables) for the Slovak Republic and by 0.54% (without control variables) and 0.38% (with control variables) for the Czech Republic.
Keywords: 330; carbon dioxide; climate change; emission; Internet